Agency conflicts, firm value, and monitoring mechanisms: An empirical evidence from Indonesia - Faisal; Muhammad Shabri Abdul Majid; A. Sakir (Cogent Economics & Finance, 2020)
Using a linear model, previous studies on the ownership concentration-firm performance nexus have produced inconsistent empirical findings and found no consensus concerning the measure of agency conflict control mechanism. Using a non-monotonic model and a combination of agency conflict control mechanisms, this study contributes to the existing literature by examining the moderating roles of additional blockholders, dividends, foreign ownership types in determining the effect of ownership concentration on performance of 580 Indonesia's firms during the 2009-2018 period. Employing panel piecewise and moderated regression models, the study documented that the ownership concentration-firm performance relationship had followed a non-monotonic pattern, proving both monitoring and expropriation hypotheses exist for non-financial firms in Indonesia. These findings highlighted the important role of additional blockholders, dividends, foreign ownership types as moderating variables, and debt as a predictor to influence firm performance, functioning as the control mechanisms for the agency conflicts in Indonesia.
Keywords: C58; G32; G35; 330; agency conflicts; firm value; Indonesia; monitoring mechanisms; ownership concentration